Генетическая нестабильность и предрасположенность к развитию опухолей у лабораторных линий мышей - Ковалева, О.А.; Вагина, И.Н.; Морозова, Л.М.; Глазко, Т.Т.; Глазко, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The different cytogenetic traits of genetic instability before the expression of phenotype changes related to the tumor development in lines BALB/c and ICR, are investigated. Two cytogenetic anomalies (aneuploidy and the asynchronous dividing of the centromeres of sister chromatides) typical of the spontaneous mutational spectra of these two lines are revealed. Presumably, these types of cytogenetic anomalies could be convenient markers of the early stages of tumor development.